BML‐111 inhibits osteoclast differentiation by suppressing the MAPK and NF‐κB pathways, alleviating deterioration of the knee joints in a CIA rat model. (5th February 2023) - Wang, Lu; Su, Wei; Zheng, Xiaohang; Lin, Wenjun; Lv, Chen; Yang, Shengwu; Chen, Bicheng; Zhang, Chunwu
Abstract: Irreversible destruction of joints is the hallmark of rheumatoid arthritis (RA). Osteoclasts are the only bone‐resorbing cells and play an important role in joint rebuilding. BML‐111 (5(S), 6(R), 7‐trihydroxyheptanoic acid methyl ester, C8 H16 O5 ) is a synthetic lipoxin A4 agonist with antioxidant and anti‐inflammatory properties. The present study aimed to investigate the effect of BML‐111 on osteoclasts in vivo and in vitro, to investigate its therapeutic effect on joint destruction in RA. Cell Counting Kit‐8 assay and flow cytometry were used to exclude cytotoxic effects of BML‐111 to bone marrow‐derived macrophages (BMMs). Then, osteoclasts were differentiated in vitro from BMMs by used macrophage colony‐stimulating factor and receptor activator of nuclear factor‐κB ligand, and osteoclasts were observed following tartrate‐resistant acid phosphatase staining with or without BML‐111 treatment. Meanwhile, absorption pit assay and immunofluorescence staining of the fibrous actin ring were used to observe osteoclast function. Moreover, we examined mitogen‐activated protein kinase (MAPK) and nuclear factor‐κB (NF‐κB) activation. We established collagen‐induced arthritis in a rat model and, after treatment with BML‐111, joint swelling was measured and the knee joints were processed for histology. We also examined serum and tissue for osteoclastogenesis‐related markers. BML‐111 inhibited osteoclast formation and differentiation in a time‐ and concentration‐dependent manner, and downregulated the expression levels of MAPK and NF‐κB in vitro. Meanwhile, BML‐111 effectively alleviated joint structural damage and inhibited osteoclast formation in vivo. BML‐111 inhibited osteoclast formation and differentiation in vitro and in vivo, and delayed the progression of joint destruction.